Exploring genetic diversity of Dahlia (Dahlia variabilis Desf.) germplasm using multivariate statistics - Simrat Singh; Kiranjeet Kaur Dhatt; Pankaj Kumar Bodla (Journal of Horticultural Sciences, 2023)
Dahlia (Dahlia variabilis) is a tuberous-rooted flower crop, exhibiting rich diversity in flower color and inflorescence form. The study was conducted to quantify diversity in 24 dahlia genotypes based on agronomic traits. The dahlia accessions were grouped based on their similarity for phenotypic resemblance following hierarchal clustering and principal component analysis (PCA). The hierarchical cluster analysis grouped the dahlia accessions into three distinct clusters viz., C1, C2 and C3 comprising 8, 3 and 13 genotypes, respectively. The 24 dahlia genotypes were found scattered across the whole variation observed by PC1 and PC2 (explaining nearly 55.2% of the cumulative total variation). The two-dimensional PCA analysis revealed that the most appropriate traits for grouping the dahlia accessions were plant height, flower weight, stalk length, vase life and number of flowers per plant. The study signifies the importance of germplasm collection, characterization and utilization of dahlia to popularize its commercial cultivation among the flower growers.